ANALISIS VARIABEL KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA SWALAYAN CITROULI BABARSARI YOGYAKARTA - Ade Ryan Shaputra; Fitroh Adhilla (Universitas Ahmad Dahlan, 2016)
This study aims to determine and analyze variables quality of service (X) to customer satisfaction (Y), simultaneously or together with customer satisfaction at Citrouli Supermarket Babarsari in Yogyakarta. The sample used in this study totaling 100 respondents. The sampling method with using purposive sampling. Data analysis method used is a quantitative analysis using the validity test and test reliability, F test, coefficient of determination, t test and multiple regression analysis. By using the method of multiple linear regression analysis can be it was concluded that the physical aspect variables had a positive effect on consumer satisfaction with a B value of 0.080 and an increase of 1 unit then the value of the physical aspects increases by 0.080, the reliability variable is influential positive on consumer satisfaction with a B value of 0.231 and increases by 1 unit then the reliability variable increases by 0.231, variable personal interaction has a positive effect on customer satisfaction with B value of 0.159 and increased by 1 unit then the personal interaction variable increased 0.159, the problem solving variable has a positive effect on consumer satisfaction with a B value of 0.241 and increased by 1 unit then the variable customer satisfaction increases 0.241, the policy variable positive effect on customer satisfaction with a B value of 0.267 and increase by 1 unit, the policy variable increases by 0.267. The resulting determination coefficient is 0.572 yang means that 57.2% of customer satisfaction variables can be explained by variables Physical Aspects (X1), Reliability (X2), Personal Interaction (X3), Solving problems (X4) and Policies (X5) together, while the rest of 42.8% explained by other variables not contained in this research.